2022
DOI: 10.3390/ijerph19052877
|View full text |Cite
|
Sign up to set email alerts
|

Povidone-Iodine as a Pre-Procedural Mouthwash to Reduce the Salivary Viral Load of SARS-CoV-2: A Systematic Review of Randomized Controlled Trials

Abstract: The use of pre-procedural rinses has been investigated to reduce the number of viral particles and bacteria in aerosols, potentially decreasing the risk of cross-infection from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during medical and dental procedures. This review aims to confirm whether there is evidence in the literature describing a reduction in salivary load of SARS-CoV-2 when povidone-iodine (PVP-I) is used as a pre-intervention mouthwash. An search of the MEDLINE, Embase, SCOPUS, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…These differences may be due to the clinical variability (different severity of the disease) of the patients included in these studies or to the variability in the methodology. García-Sánchez et al [ 34 ] conducted a systematic review of RCTs and reported a significant virucidal capacity of povidone-iodine at 0.5% and 1%. However, they did not find a benefit in the reduction of SARS-CoV-2 viral load in saliva with the 2% concentration at 30 and 60 s. However, they state that the evidence is currently uncertain and that more RCTs are required.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be due to the clinical variability (different severity of the disease) of the patients included in these studies or to the variability in the methodology. García-Sánchez et al [ 34 ] conducted a systematic review of RCTs and reported a significant virucidal capacity of povidone-iodine at 0.5% and 1%. However, they did not find a benefit in the reduction of SARS-CoV-2 viral load in saliva with the 2% concentration at 30 and 60 s. However, they state that the evidence is currently uncertain and that more RCTs are required.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupting host cell attachment by inactivating receptors to limit viral infection is an obvious choice for infection control in community and healthcare settings for both unexposed and higher risk staff. 35 Lungs are the prime receptor organs of ACE2 followed by the oral cavity. The oral cavity is the best potential site of SARS-CoV-2 invasion because of saliva.…”
Section: Recent Research Evidencementioning
confidence: 99%
“…21 However multiple studies show that using mouthwash, or the gargle method, or as an oral rinse and even delivery via the nasopharynx can reduce viral load. 21,25,32,33,35 Research trials targeting the nose used 0.5% PVP-I with low-dose volume 0.33ml daily consumption. Used as a mouth wash or as a gargle with PVP-I 1% every 2-3 hours or up to 4 times daily was also effective.…”
Section: In Vivo Efficacy Of Povidone-iodinementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, oral care is important for prevention of transmission of SARS-CoV-2.Mouthwash has been focused on preventing microbiome infection 16 . In addition, several components of mouthwash have recently been reported to reduce SARS-CoV-2 virions in the oral cavity 17,18 . Cetylpyridinium chloride (CPC) is widely used as one of the bactericidal components of mouthwash, tablets, sprays, and drops.…”
mentioning
confidence: 99%